Butt Why? Exploring factors associated with cigarette scavenging behaviors among adult smokers enrolling in a clinical trial for smoking cessation. (March 2018) - Lantini, Ryan; Sillice, Marie A.; Fava, Joseph L.; Jennings, Ernestine; Rosen, Rochelle K.; Horowitz, Santina M.; Becker, Bruce M.; Bock, Beth C.
Abstract: Introduction: Cigarette smoking is associated with many adverse health effects and is an important public health concern. Increased understanding of smokers' behavior is central to developing effective interventions. Cigarette scavenging, a behavior that involves smoking shared or previously used cigarettes has thus far only been shown to be prevalent among homeless or incarcerated populations. The current study examines whether cigarette scavenging is prevalent in a more general population of adult smokers enrolling in a smoking cessation clinical trial, and whether engagement in this behavior is associated with demographic or smoking-related psychosocial factors. Methods: Baseline data was obtained from adult smokers (N = 227) enrolling in a randomized clinical trial for smoking cessation. Cigarette scavenging was assessed using three items: a) sharing a cigarette with a stranger; b) smoking a "found" cigarette and c) smoking a previously used cigarette "butt". Participants who endorsed engaging in at least one of these three behaviors were categorized as a scavenger. Results: Approximately 32% of participants endorsed at least one cigarette scavenging behavior. A multiple logistic regression analysis found that scavengers were more likely to be: men (p < 0.001), of younger age at smoking onset (p = 0.012), unemployed (p = 0.003), more likely to have used marijuana in the past 30 days (p = 0.005), single or living alone (p = 0.003), and to have experienced higher withdrawal symptoms during previous quit attempts (p = 0.044) as compared to non-scavengers. Conclusions: Scavenging is common among adult smokers. Interventions that address cigarette scavenging behaviors may better meet the needs of this unique smoking subgroup. Highlights: Cigarette scavenging is a smoking behavior involving shared or previously used cigarettes. This behavior has not yet been assessed in a general population of adult smokers. 31.7% of study participants were classified as cigarette scavengers. Significant differences were observed between scavengers and non-scavengers. Interventions addressing these behaviors may meet the needs of this subgroup of smokers.